Biogeography and evolution of Thermococcus isolates from hydrothermal vent systems of the Pacific - Price, Mark T.; Fullerton, Heather; Moyer, Craig L. (Frontiers in Microbiology, 2015)
Thermococcus is a genus of hyperthermophilic archaea that is ubiquitous in marine hydrothermal environments growing in anaerobic subsurface habitats but able to survive in cold oxygenated seawater. DNA analyses of Thermococcus isolates were applied to determine the relationship between geographic distribution and relatedness focusing primarily on isolates from the Juan de Fuca Ridge and South East Pacific Rise. Amplified fragment length polymorphism (AFLP) analysis and multilocus sequence typing (MLST) were used to resolve genomic differences in 90 isolates of Thermococcus, making biogeographic patterns and evolutionary relationships apparent. Isolates were differentiated into regionally endemic populations however there was also evidence in some lineages of cosmopolitan distribution. The biodiversity identified in Thermococcus isolates and presence of distinct lineages within the same vent site suggests the utilization of varying ecological niches in this genus. In addition to resolving biogeographic patterns in Thermococcus, this study has raised new questions about the closely related Pyrococcus genus. The phylogenetic placement of Pyrococcus type strains shows the close relationship between Thermococcus and Pyrococcus and the unresolved divergence of these two genera.